Analisis Pengaruh Motivasi, Kepuasan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Di PD. BPR BKK Wonogiri - Eka Kusuma Dewi, Rahayu; , Dr. Edy Purwo Saputra, S.E., M.Si (2017)
This research aimed to analyses influence of motivation, work satisfaction and work discipline to employee's performance in PD. BPR BKK Wonogiri. Population and sample used at this research is employees in PD. BPR BKK Wonogiri amounting to counted 30 respondents. Data collecting of method used by questioner. Hypothesis tested in this research use analyzer validity test, reliabilities test, classic assumption test, doubled linear regression, F test, t test, and coefficient of determinacy (R2). Result of research indicate that motivation, work satisfaction and work discipline have an effect on positive to employees performance in PD. BPR BKK Wonogiri. Motivation, work satisfaction and work discipline by simultant have an effect on positive to employee's performance in PD. BPR BKK Wonogiri. Result of Test coefficient of determinacy (R2) show employees performance in PD. BPR BKK Wonogiri influenced by motivation, work satisfaction and work discipline equal to 87,6%, and the model have got away from examination of classic assumption. Keywords: Motivation, Work Satisfaction, Work Discipline and Employees Performance.